MORBIDITY OF SURGERY IN PREVIOUSLY UNDIAGNOSED CIRRHOTIC PATIENTS - Maqsood, Rasikh; Rasikh, Alia; Iqbal, Zahoor; Asghar, Muhammad Usman; Abbasi, Tariq (Journal of Ayub Medical College Abbottabad, 2015)
Background: Undiagnosed cirrhotic patients are frequently encountered during routine and emergency surgery. These patients have a higher incidence of blood loss & wound infection, resulting in prolonged hospital stay. This study was conducted to highlight the possible complications which result in prolonged hospital stay in these patients. Methods: A total of 38 patients were incidentally found to have cirrhosis out of a total of 1560 patients who underwent abdominal operation. Diagnosis was confirmed on per-operative liver biopsy and was suspected preoperatively in patient having abnormal liver function test. Per-operative bleeding, postoperative wound infection and hospital stay was compared in cirrhotic and non-cirrhotic patients. Results: The mean blood loss was 310 ml in cirrhotic patients as compared to 205 ml in non-cirrhotic patients which was statistically significant (p-value 0.008). Post-operative infection rate was 21% in cirrhotic patients compared to non- cirrhotic patients 5%. Significance was tested using Pearson Chi square test (0.042). The Average hospital stay was 10 days in cirrhotic patients and 7.5 days in non-cirrhotic patients respectively which was statistically significant (p-value 0.006). Conclusion: There is statistically significant difference in per-operative bleeding, wound infection and hospital stay in cirrhotic and non-cirrhotic patients.